The open subject and translations from nature: Answers to the Anthropocene in contemporary poetry (Gennadij Ajgi, Les Murray, Christian Lehnert) - Stahl, Henrieke (The anthropocene review, 2022)
With the help of the concepts ‘aura’ and ‘autopoiesis’, the relationship between poetry and natural phenomena can be defined as a ‘translation from nature’. Gennadij Ajgi translates his auratic manner of perceiving into poetry. For him, the poem becomes an epistemic medium transcending the sensory perception of nature for a hidden, spiritual level. Les Murray, conversely, demonstrates an autopoietic understanding of nature: The poet himself becomes the medium of the living being. Christian Lehnert takes up impulses from both orientations. He combines the opposing concepts so that they correspond to the hierarchical levels of his religious and metaphysical vision of the world. The three authors all aim to alter the attitude of humans towards nature through their ‘translation from nature into poetry’ so that humankind will open itself towards nature and raise it from an object which can be instrumentalised to an autonomous subject on equal footing with humanity itself.